Phaeohyphomycosis caused by Phialophora americana in a dog. Issue 5 (31st May 2022) - Martini, Franco; Seehusen, Frauke; Krudewig, Christiane; Beckmann, Katrin M.; Favrot, Claude; Fischer, Nina M.; Guenova, Emmanuella; Rostaher, Ana
Abstract: Phaeohyphomycosis was diagnosed in a 6‐year‐old, male castrated Dachshund on immunosuppressive treatment. The fungus was identified by culture and PCR as Phialophora americana . This is the first reported case of infection with this pathogen in a dog. The infection was successfully managed medically, without surgical intervention. Abstract : Phaeohyphomycosis was diagnosed in a 6‐year‐old, male castrated Dachshund on immunosuppressive treatment. The fungus was identified by culture and PCR as Phialophora americana . This is the first reported case of infection with this pathogen in a dog. The infection was successfully managed medically, without surgical intervention. Résumé: Une phaéohyphomycose a été diagnostiquée chez un teckel mâle castré de 6 ans sous traitement immunosuppresseur. Le champignon a été identifié par culture et PCR comme Phialophora americana . Il s'agit du premier cas rapporté d'infection par cet agent pathogène chez un chien. L'infection a été prise en charge médicalement avec succès, sans intervention chirurgicale. Resumen: Se diagnosticó feohifomicosis en un macho de Teckel castrado de 6 años en tratamiento inmunosupresor. El hongo fue identificado por cultivo y PCR como Phialophora americana . Este es el primer caso reportado de infección por este patógeno en un perro. La infección se manejó con éxito médicamente, sin intervención quirúrgica. Zusammenfassung: Eine Phäohyphomykose wurde bei einem 6 Jahre alten kastrierten Dackelrüden, der eine immunsuppressive Behandlung erhielt, diagnostiziert. Der Pilz wurde mittels Kultur und PCR als Phialophora americana identifiziert. Es handelt sich hierbei um den ersten Fallbericht einer Infektion mit diesem Pathogen bei einem Hund. Die Infektion wurde erfolgreich – ohne chirurgische Intervention ‐ medizinisch gemanagt. 要約: 免疫抑制療法を受けている6歳の去勢雄のダックスフンドに黒色菌糸症が発生した。培養検査およびPCR法により真菌は Phialophora americana と同定された。本症例は、犬における本菌の感染症例として初めての報告である。本症例は、外科的手術を行うことなく、内科的治療で治癒した。 摘要: 一名接受免疫抑制治疗的6岁去势雄性腊肠犬，在其身上诊断出暗色丝孢霉病。经培养和PCR鉴定该真菌为美洲瓶霉(Phialophora americana)。这是首次报道的犬感染该病原体的病例。通过药物成功治疗了感染，未进行手术干预。 Resumo: Feohifomicose foi diagnosticada em um cão da raça Dachshund, macho castrado, de seis anos de idade, em tratamento imunossupressivo. O fungo identificado por cultura e PCR foi Phialophora americana . Este é o primeiro relato de caso de infecção por este patógeno em um cão. A infecção foi bem conduzida com tratamento medicamentoso, sem intervenção cirúrgica.